Appropriate technologies for third world development : proceedings of a conference held by the International Economic Association at Teheran, Iran - Robinson, Austin; International Economic Association (London : Macmillan, 1979)
The conference that is recorded in this volume represents the latest in a long series of conferences that the International Economic Association has devoted to the various aspects of the development of the poorer 'third world' countries. The purpose of the conference was to rather pose questions: How far in the actual practice of current development are 'appropriate technologies' being used? And if not, why not? What are the reasons?
Includes bibliographical references and index.
ne 29/03/2018
Loans
Keywords: Underdeveloped areas-- Technology-- Congresses; Appropriate technology; Technology